An analytical exploration of barriers to resilient circular food supply chains using integrated structural methods - Emel Yontar (Supply Chain Analytics, 2025)
This study addresses the critical research problem of how to achieve resilience in food supply chains transitioning from linear to circular models. While circular food supply chains aim to enhance sustainability, reduce waste, and improve resource efficiency, they face complex systemic barriers that make resilience a challenging goal. To explore these barriers, the research adopts a hybrid methodological framework combining Interpretive Structural Modeling (ISM), MICMAC analysis (Cross-Impact Matrix Multiplication Applied to Classification), and the Decision-Making Trial and Evaluation Laboratory (DEMATEL) method. This integrative approach enables the identification and classification of key obstacles based on their hierarchical structure and interdependence. The findings reveal that legal uncertainties and lack of incentives, financial difficulties, and technological immaturity are the most influential root barriers undermining Circular Economy-oriented Food Supply Chain Resilience (FSCR). These insights provide a structured understanding of the cause-effect relationships between challenges, offering practical guidance for policymakers, practitioners, and researchers seeking to build resilient and circular food supply chains amid increasing global disruptions.